Cross-Talk Between Large Artery Stiffness and Retinal Microvasculature in Children: The ExAMIN Youth SA Study - Breet, Yolandi; Craig, Ashleigh; Smith, Wayne; Botha-Le Roux, Shani; Gafane-Matemane, Lebo F.; Brits, Sanette; Rooyen, Johannes M. van; Hanssen, Henner; Kruger, Ruan (Frontiers in Pediatrics, 2021)
Background: Cross-talk between the macro-and microvasculature is considered an important contributor to target organ damage. Previous findings were predominantly in adult populations and investigation into this mechanism in children may provide insight into the development of early adverse vascular changes. Whether any ethnic differences in cross-talk is evident, also remains to be determined. Objective: To determine whether retinal microvascular diameters are associated with large artery stiffness in young children and whether ethnic differences are evident. Materials and methods: In this cross-sectional study, 730 black (n=437) and white (n=293) school children aged 5-9 years were included. Pulse wave velocity (PWV) was measured and the central retinal arteriolar equivalent (CRAE) and central retinal venular equivalent (CRVE) diameters were calculated from fundus images. The arterio-venous ratio (AVR) was subsequently calculated. Results: Pulse wave velocity was lower (p≤0.001) in the black group when compared to the white group. The black group had a narrower CRAE, wider CRVE and lower AVR (all p<0.001). Pulse wave velocity associated negatively with CRAE (r=-0.141, p=0.003) and AVR (r=-0.185, p≤0.001) in the black group only. A positive association between PWV and CRVE was seen in the black (r=0.174, p≤0.001) and white (r=0.119, p=0.043) group. Conclusion: Large artery stiffness is associated with retinal arterial narrowing and venular widening in children, suggesting cross-talk between the macro-and microvasculature. Ethnic differences in these associations are also evident. Our findings warrant further investigation into environmental and sociocultural risk factors contributing to premature cardiovascular disease development.